2019
DOI: 10.1016/j.rmed.2018.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Emerging concerns of infectious diseases in lung cancer patients receiving immune checkpoint inhibitor therapy

Abstract: Cancer immunotherapy using immune checkpoint inhibitors has received a remarkable amount of attention in patients with non-small cell lung cancer (NSCLC). The unique adverse effects known as immunerelated adverse events (irAEs) associated with immune checkpoint inhibitors are not known however, and neither is the incidence of infectious disease among patients receiving immune checkpoint inhibitors. The aims of this study were to investigate the incidence of infections during nivolumab treatment, and the risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
88
4
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(101 citation statements)
references
References 14 publications
7
88
4
2
Order By: Relevance
“…Another study of 167 NSCLC patients treated with nivolumab reported that 33 infections occurred in total, of which 25 were bacterial, two were fungal and six were viral. Diabetes mellitus was an independent risk factor for infection …”
Section: Clinical Data Review and Description Of Potential Mechanism mentioning
confidence: 99%
See 4 more Smart Citations
“…Another study of 167 NSCLC patients treated with nivolumab reported that 33 infections occurred in total, of which 25 were bacterial, two were fungal and six were viral. Diabetes mellitus was an independent risk factor for infection …”
Section: Clinical Data Review and Description Of Potential Mechanism mentioning
confidence: 99%
“… Pneumonia is the most common infection in patients with irAEs . For patients with signs of infection, initiation of empirical antimicrobial treatment as soon as possible is advised, while further microbiological examinations are needed to identify pathogens.…”
Section: Treatmentsmentioning
confidence: 99%
See 3 more Smart Citations